Koncentracija imatiniba v plazmi - nov laboratorijski podatek pri spremljanju zdravljenja slovenskih bolnikov s kronično mieloično levkemijo - Mlakar, Jernej (Zdravniški vestnik, 2011)
Background: In past ten years imatinib (IM) has greatly improved the prognosis of patients with chronic myeloid leukemia (CML). However, 30 % of patients still fail to achieve treatment goals or cannot maintain them later. In the last three years, Imatinib plasma concentration (IPC) has been mentioned as a possible influence on treatment success. Therefore, for the first time in Slovenia, we searched for possible connection between IPC and treatment success defined as a major molecular response (MMR) until 18 months of treatement. Patients and methods: We included 75 patients with CML who had been receiving IM at that time of the study and were diagnosed in a chronic or accelerated phase of CML. Blood samples for IPC determination were sent to areference laboratory in Bordeaux. We set up a method of IPC determination in Slovenia. Results: Association between IPC and MMR achievement until 18 months of tretment was not statistically significant in patients receiving 400 mg of imatinib (p = 0.30). Age and time from the second to last dose of IM were not associated with IPC (p = 0.47 and 0.80, respectively), while gender and dose were (p for both < 0.01). Conclusions: There was no clear correlation between IPC and MMR achievement until 18months of treatment. We conclude that IPC determination would be rational in patents who fail to meet the generally accepted criteria for treatment success, in patients who experience severe side effects of IM, or patients receiving drugs that cause a pharmacokinetic interference with IM.
Keywords: imatinib; kronična mieloična levkemija; levkemija; therapy; zdravljenje